Collective trauma in Ukraine: realities and prospects of the multigenerational legacies research - Frankova Ірина; Chaban Олег; Petrenko Георгій; Tokarchuk Анастасія (Psychosomatic Medicine and General Practice, 2023)
Introduction. Ukraine is experiencing a great upheaval - a large-scale war. This distressing situation affects the entire population of the country, therefore, beyond any doubt, the term "collective traumatization" can be used for today’s situation in Ukraine. Modern research and study of the impact of collective trauma in Ukraine refers to the analysis of its negative consequences on various spheres of life, including the sphere of mental health: identification of the level of anxiety, psychological consequences, symptoms of posttraumatic stress disorders. Although, the study of the impact of a powerful collective trauma on future generations Ukrainians needs timely planning and preparation. The aim of study: to conduct a theoretical analysis of approaches to the study of the concept of "collective trauma", to study the concept of memory in the understanding of collective trauma, to analyze the peredictors and preventors of transgenerational transmission of collective trauma, to consider the epigenetic mechanisms of collective trauma, to investigate the research psychometric tools on the transmission of transgenerational trauma between generations, to investigate the specifics of the collective trauma of the population of Ukraine. Method. A literature search was conducted in the scientific databases of Web of Science, Scopus, Pub Med, Google Scholar using the keywords "collective trauma", "traumatic memory", "transgenerational trauma", "cultural trauma", "multigenerational legacies of trauma" in the period from 2002 to 2023. 17,720 sources were identified. Inclusion criteria were: (a) controlled randomized research (b) on preventors and predictors of transmission of collective trauma (c) to subsequent generations. The results. 46 international publications were included in the literature review, and predictors and preventers of the transmission of trauma through generations were analyzed from the standpoint of attachment theory, family systems, and epigenetics. Most authors note the presence of a link between the parents’ trauma and the mental health of the offspring, the greater intensity of the reparative adaptive styles the greater is the risk of developing affective or anxiety disorders in the offspring. The studies of epigenetic mechanisms of the transgenerational impact of trauma have shown the presence of changes in the methylation of the FKMB-5 gene in Holocaust survivors and their descendants. The collective trauma experienced by the people of Ukraine at the times of war has its own specificity, which distinguishes it from other collective traumas, including those experienced directly by the Ukrainian people in the past (the Holodomor, the Second World War, the Holocaust, the disaster at the Chernobyl Nuclear Power Plant). In order to further conduct research and study the transmission of war trauma in Ukraine through subsequent generations and to identify possible factors of resistance, the "Danieli Inventory of Multigenerational legacies of trauma" was adapted for the Ukrainian context of war (Appendix 1). Conclusions. Research on a topic of multigenerational legacies of collective trauma is a debatable issue. Research on factors of transgenetic changes in large groups in Ukraine is needed. Research on the next generations should include (a) large-scale genetic studies, (b) analysis on plevalence and distribution of mental health disorders in children of war veterans and the survivors of collective trauma, (c) changes in social behavior of the new generations.